Profile study of PREP users (HIV pre-exposure prophylaxis) in the Municipality of Cascavel (Research, Society and Development, 2022)
Seen as a new way of not contracting the Human Immunodeficiency Virus (HIV), which causes a notifiable disease, the daily taking of a pill, legally prescribed and indicated by a medical professional specialized in the area, seeks pre -exposure to the virus in patients belonging to risk groups. A medication recently implemented and accepted on the list of approved drugs and distributed free of charge to the population through the Unified Health System (SUS), by the National Health Surveillance Agency (ANVISA). Due to the great impact on the patients' quality of life and socioeconomic factors, this study seeks to analyze which population groups are candidates for the use of medication, recognized and approved by the Ministry of Health and how they are distributed in society, analyzing the epidemiological profile of patients, in Municipality of Cascavel – Paraná, in comparison with the numbers of the state of Paraná and the country Brazil. From the interpretation of the data, collected from an electronic address provided by the department of diseases, chronic conditions and sexually transmitted infections of the ministry of health, recognize the possibility of maintaining or establishing new measures in search of a more complete and optimized treatment in favor of wellfare of the patient.